2013
DOI: 10.1007/s11064-013-1228-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Function of κ-Carrageenan Oligosaccharides Acting on LPS-Activated Microglial Cells

Abstract: The major neurodegenerative diseases are characterized by increasing of activated-microglial cells and inflammatory cytokines in the central nervous system. Carrageenan extracted from red algae is a kind of polysaccharide with sulfate groups. The oligosaccharides were obtained from carrageenan by enzymatic degradation. To detect the immunomodulatory activity of κ-carrageenan oligosaccharides (KOS) on microglial cells and the relationship to the sulfate group content, the desulfated derivatives of KOS (DSK) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Numerous studies have revealed the inherent beneficial effects of AOS and COS for human health, including prebiotic effects [ 10 , 11 ], immuno-modulatory [ 87 ], anti-inflammation [ 88 ], anti-oxidant [ 6 , 46 ], and anti-tumor [ 89 ] activities. A compilation of some noteworthy observations in this direction is presented in the following paragraphs.…”
Section: Biological Activities Of Oligosaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have revealed the inherent beneficial effects of AOS and COS for human health, including prebiotic effects [ 10 , 11 ], immuno-modulatory [ 87 ], anti-inflammation [ 88 ], anti-oxidant [ 6 , 46 ], and anti-tumor [ 89 ] activities. A compilation of some noteworthy observations in this direction is presented in the following paragraphs.…”
Section: Biological Activities Of Oligosaccharidesmentioning
confidence: 99%
“…AOS and COS have a range of immune-modulatory and anti-inflammatory effects in mucosal and metabolic tissues. COS can protect microglial cells from being activated by lipopolysaccharide (LPS), and its inhibitory function is related to the sulfate group content of COS [ 87 ]. Likewise, carrageenan and COS have been reported to stimulate the induction of interleukin (IL)-10 in human and mice blood cells, with COS inducing more IL-10 in vivo than carrageenan [ 93 ].…”
Section: Biological Activities Of Oligosaccharidesmentioning
confidence: 99%
“…Besides this, κ-carrageenan has exhibited prominent biological effects, including antitumor [138], antioxidant [139] and anti-inflammatory [140]. Regarding to neurodegenerative diseases, studies have already showed that κ-carrageenan was able to protect microglial cells against LPS toxicity through the reduction of the viability and content of • NO, TNF-α and IL-10 [140,141]. The authors suggested that the protective function of κ-carrageenan was positively correlated to the sulfate group content of the studied oligosaccharides [140,141].…”
Section: Neuroprotective Compounds From Macroalgaementioning
confidence: 99%
“…Regarding to neurodegenerative diseases, studies have already showed that κ-carrageenan was able to protect microglial cells against LPS toxicity through the reduction of the viability and content of • NO, TNF-α and IL-10 [140,141]. The authors suggested that the protective function of κ-carrageenan was positively correlated to the sulfate group content of the studied oligosaccharides [140,141]. Therefore, κ-carrageenan can potentially be used for preventing the neurodegenerative processes of some CNS diseases.…”
Section: Neuroprotective Compounds From Macroalgaementioning
confidence: 99%
“…Carrageenan is an abundant water-soluble sulfated polysaccharide extracted from red algae that has been widely used in the food industry as an emulsifier, stabilizer or thickener due to its physicochemical stability, safety and affordability [ 8 ]. In recent decades, the biological activities of carrageenan have been investigated, including anti-coagulant [ 9 ], anti-tumor [ 10 ], and immunomodulatory activities [ 11 , 12 ]. In addition, carrageenan can inhibit a broad range of DNA viruses [ 13 ] such as papillomavirus [ 14 , 15 ] and herpes simplex virus [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%